Pengaruh Gaya Kepemimpinan dan Stres Kerja Terhadap Turnover Intention pada PT DCBA Jakarta Selatan - Muhammad Tegar Irsyadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study was to examine the effects of leadership style and work stress on turnover intention. A quantitative approach was employed, with the research focusing on a causal, or cause-and-effect, relationship. Data were collected through surveys using questionnaires distributed to participants selected as the study's subjects. Causal research aims to identify the cause-and-effect relationships between variables, specifically the independent and dependent variables. This study utilized a saturated sampling technique, where the entire population—comprising 35 employees—was included in the sample. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis was conducted using the Smart PLS 3.2.9 software. The study's findings revealed that leadership style directly influences turnover intention, while work stress does not significantly impact turnover intention.